1996
DOI: 10.1084/jem.184.3.971
|View full text |Cite
|
Sign up to set email alerts
|

An Epstein-Barr virus-associated superantigen.

Abstract: More than 90% of adults are latently infected with Epstein-Barr virus (EBV), the causative agent of infectious mononucleosis, a self-limiting lymphoproliferative disease characterized by extensive T cell activation. Reactivation of this herpesvirus during immunosuppression is often associated with oncogenesis. These considerations led us to analyze the early events that occur after exposure of the immune system to EBV. Strong major histocompatibility complex (MHC) class II- dependent but not MHC-restricted, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 51 publications
1
86
0
1
Order By: Relevance
“…HERV-K18 is a relatively recent integrant in the genome, as it is found in Old World primates but not in New World primates, indicating that it was acquired subsequent to the evolutionary divergence of these species (28). A few years ago, it was reported that Epstein-Barr virus (EBV) is associated with TCRBV13-specific superantigen activity, which is MHC class II dependent and not due to a recall antigen response (53). More recently, it was demonstrated that the superantigen activity is due to EBV transactivation of HERV-K18 env (52).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HERV-K18 is a relatively recent integrant in the genome, as it is found in Old World primates but not in New World primates, indicating that it was acquired subsequent to the evolutionary divergence of these species (28). A few years ago, it was reported that Epstein-Barr virus (EBV) is associated with TCRBV13-specific superantigen activity, which is MHC class II dependent and not due to a recall antigen response (53). More recently, it was demonstrated that the superantigen activity is due to EBV transactivation of HERV-K18 env (52).…”
mentioning
confidence: 99%
“…We simultaneously assessed activation of TCRBV8 T-cell hybridomas as a specificity control. Hybridoma assays were performed as described previously (52,53) by using the TCRBV13 T-cell hybridoma, hV␤13.1-1 (11,12) and the TCRBV8 T-cell hybrid YL␤8#24 (53). Figure 1A depicts the results of a representative hybridoma assay with two lymphoblastoid cell lines (LCL), Mg68 and 253.30, that were derived by transformation with EBV deletion mutants lacking the majority of the lytic genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the inability of the immune system to control EBV-infected B lymphocytes is partly due to defects in Th cell responses (15,20,37). To investigate this hypothesis, we generated continuously growing CD4 Th cells of XLP patients using herpesvirus saimiri (HVS).…”
mentioning
confidence: 99%
“…Incompatibility for Mtv is not particularly associated with this genetic combination since all strains of mice display a specific pattern of two to eight endogenous proviruses in their genome. 28 and cytomegalovirus 29 were shown to be associated with superantigenic responses stimulating V␤13 + and V␤12 + T cells, respectively. Interestingly, the presence of these infectious agents is known to increase the risk of GHVD in grafted patients.…”
Section: Discussionmentioning
confidence: 99%